2022
DOI: 10.3389/fphar.2022.1014658
|View full text |Cite
|
Sign up to set email alerts
|

Institutionalizing health technology assessment in Egypt: Situational analysis and roadmap

Abstract: Objective: To conduct a situational analysis with the aim to inform future health technology assessment efforts (HTA) in Egypt.Introduction: The Egyptian government has set universal health coverage as a 2030 target. Several agencies have been created in the context of the ongoing healthcare reform. The Egyptian Authority for Unified Procurement, Medical Supply and the Management of Medical Technology (UPA) is one of them and was established to support strategic procurement using HTA.Methods: Description of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…This study provides invaluable information with Iran’s MOHME, MCLSW and government and private insurance organizations as the primary users of HTA, which is consistent with findings from precursory studies [ 1 , 22 , 25 ] and the WHO report. As custodians of health within their respective countries, these organizations bear the responsibility of providing services through the utilization of various technologies and ensuring their financial coverage.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This study provides invaluable information with Iran’s MOHME, MCLSW and government and private insurance organizations as the primary users of HTA, which is consistent with findings from precursory studies [ 1 , 22 , 25 ] and the WHO report. As custodians of health within their respective countries, these organizations bear the responsibility of providing services through the utilization of various technologies and ensuring their financial coverage.…”
Section: Discussionsupporting
confidence: 85%
“…Health technology assessment (HTA) encompasses a comprehensive and multidisciplinary process aimed at evaluating the various dimensions of a health technology’s value, which may include aspects such as clinical, economic, social and ethical considerations [ 1 ]. The primary objective of HTA is to furnish decision-makers with evidence-based information to facilitate informed healthcare policies, clinical practices and funding choices.…”
Section: Introductionmentioning
confidence: 99%
“…The policy areas with a potential need for HTA and the corresponding organizations that can use HTA outputs in Zimbabwe were identified. The policy areas and organizations that need HTA identified in this study were similar to those reported in studies carried out in Nigeria and Egypt (20;23). However, in this study, lower levels of demand for health economic and social/ethical evidence were reported across all the listed organizations.…”
Section: Discussionsupporting
confidence: 81%
“…Stakeholder mapping and analysis were independently performed by two researchers using a checklist developed by the International Decision Supportive Initiative (iDSI) (19). This checklist has recently been used to determine relevant HTA stakeholders in the Egyptian context (20), and it characterizes stakeholders into nodes, networks and, environments, based on the capacity-building framework of the iDSI (21). For each category of stakeholders, the tool suggests a set of questions that help identify relevant stakeholders for a particular country.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation